Penerimaan Audiens Terhadap Gangguan Mental Dalam Film Selesai - Riadi, Sonya Gringsing; Rahmawati, Aulia (Jurnal Representamen, 2022)
Selesai tells a story about affair issues and mental illness issues which is a plot twist in the movie. Mental illness became something controversial in society. The purpose of this study was to determine the audience’s acceptance of mental illness in the Selesai movie. This research uses descriptive qualitative analysis method with reception analysis approach through Stuart Hall’s encoding-decoding. The data acquisition method used is indepth interview with seven informants. The result of this research is that audience is divided into three positions that is dominant-hegemonic, negotiated, and oppositional. Audience who are in the dominant-hegemonic position agrees and accepts the overall mental illness in the Selesai movie. Audience who are in the negotiated positions gave a positive respone to the film, but rejected the depiction of mental illness in the movie because they believed that the media interfered in constructiong it excessively and not in accordance with what is experienced. Meanwhile, the audience who are in oppositional positions considered that the mental illness on the Selesai movie were contrary to the values they believed in. the audience’s acceptance was motivated by various factors such as frame of references and field of experience.